Has the human biological interaction with SARS‐CoV2 variants entered a pliant "Faustian bargain"? - Richard J. Head; Marko Popovic; Jennifer H. Martin (Wiley, 2024)
Abstract We hypothesize that a "Faustian bargain"-the trading of increased SARS-CoV2 viral infection with a concurrent potential for prevention of life‐threatening lower lung infection explains the previous and future morbidity and mortality from COVID‐19. Further, this trade‐off is made feasible by fundamental principles of thermodynamics and receptor affinity.